Penerapan Teknik Relaksasi Napas Dalam Terhadap Penurunan Intensitas Nyeri Pada Pasien Gastritis Tn. A.K Di Ruangan C2 RS. R. D. Kandou Manado - Manengkey, Olvin; Bunaen, Monalisa (Yayasan Syalom Cipta Sumikolah, 2025)
Gastritis is inflammation of the gastric mucosa caused by irritation and infection. Gastritis can occur suddenly (acute gastritis) or gradually (chronic gastritis). Gastritis includes inflammatory processes or health problems caused by irritation and infection factors in the gastric mucosa and submucosa. Gastritis is commonly known as ulcer disease. The aim of this research is to gain real experience and knowledge and be able to document the application of deep breathing relaxation techniques to pain intensity in gastritis nursing care. This research method is this type of scientific writing using a descriptive method with a case study approach to explore the problem of nursing care for patients with gastritis. Nursing care was provided to the patient Mr. A.K was carried out on 18-19 Juni 2024. From the results of nursing care for Mr